Micronutrient deficiencies and cardiac health - Rehman, Shazia; Jianglin, Zhang (Frontiers in Nutrition, 2022)
Inadequate diet and nutritional quality are potentially correlated with an escalated risk of cardiac-related morbidity and mortality. A plethora of knowledge is available regarding the influence of heart-healthy dietary patterns in response to disability-adjusted life years (DALYs), yet little is known regarding the best approaches to adopt. In response, the present investigation aims to bridge this knowledge gap by implementing mathematical machine learning grey methodology to assess the degree of influence and the potential contributing factors in DALYs due to ischemic heart disease and stroke, in conjunction with the Hurwicz (Min-Max) criterion. The outcomes highlighted that a diet low in fruits is a potential contributor to IHD-related DALYS, whereas a diet low in vegetables is a more grounded contributor to stroke-related DALYs in Spain, among others. Moreover, the Hurwicz approach highlighted IHD to be more impacted due to dietary and nutritional factors than stroke. In conclusion, our investigation strongly supports a balanced diet and precision nutrition guidelines as a strategy for reducing cardiac-related diseases in the Spanish population. It is a public health primary consideration to build an ambiance that encourages, rather than hinders, compliance with cardioprotective dietary practices among all people.